Error Analysis On Written Production Made By The Second Year Students Of SMU Negeri 1 Ngemplak Boyolali In 2003/2004 Academic Year - Fitriasih, Dewi (2004)
The purposes of the research are to describe (1) the types of error, (2) the frequency of error, (3) the dominant of error and, (4) the source of error. Therefore, the method used by the researcher is descriptive ones. The research was conducted to the second year students of SMU Negeri 1 Ngemplak Boyolali 2003/2004 Academic Year. There were 45 students are taken as the subject of the research. The object of the research is erroneous sentences taken from written production made by the students. The data of the research is erroneous sentences and the data source is written production made by 45 students. Dealing with the research instrument of collecting the data, the researcher uses a test that is written production. From the result of the test the researcher get the data to be analyzed. The collecting data then were analyzed descriptively by means of Error Analysis. In analyzing the data, the researcher uses procedures of Errors Analysis, they are: identification, description and explanation. Based on the analysis of the data, the result of the research shows that there are 134 erroneous sentences. The errors are analyzed based on Linguistic Category. There are 7 types of errors, they are: the use of present tense (25.3%) that includes additional of to be in the present tense (14.9%), omission of -s/-es in the verb of present tense (1.5%), the use of verb-ing in the present tense (1.5%), the use of have instead has in the present tense (5.2%), the use of past tense in the present tense (1.5%), and disagreement of subject and verb in the present tense (0.7%). Then, the use of noun phrase (26.1%) includes substitution of singular to plural (13.4%), the use of much instead many (3.7%), the use of noun instead verb (3.0%), false concept sentence (4.5%), and in word order (4.5%). The category of the use of verb phrase (16.5%) includes omission of to be (7.5%), misuse of verb after auxiliaries (7.5%), and misuse of to be (1.5%). The category of the use of infinitive marker "to" (10.4%) includes additional of unnecessary infinitive marker "to" (8.9%) and omission of infinitive marker "to" (1.5%). The category of the use of pronouns (5.1%) includes the use of subject instead possessive adjective (2.2%), the use of subject instead of objective pronoun (2.2%), the use of object as subject (0.7%). Then, the category of some transformation (2.9%) includes formation of no or not without the auxiliary do in the negative transformation (2.2%), omission of subject (0.7%). The last category is misspelled word (13.4%). The dominant type of error is additional of to be in the Present Tense (14,9%) with the total number of errors are 20 erroneous sentences. There are two sources of error, namely interlingual transfer and intralingual transfer. The result of this research is that the most of students are still making a lot of errors in written productions, especially grammatical errors.